The Indonesian's Road Transportations as The Contexts to Support Primary School Students Learning Number Operation - Kairuddin Kairuddin; Darmawijoyo Darmawijoyo (Journal on Mathematics Education, 2011)
This paper highlights the Indonesian's road transportation contexts, namely, angkot, that used in learning and teaching of addition and subtraction in first grade and second grade MIN-2 Palembang. PMRI approach that adopt from RME was used in this design research. From teaching experiment was founded that the student used many strategies when teaching and learning process conducted. In situational level they used their knowledge of experience-base activity, in referential level they use manik-manik (string of beads), and in general level they used number line to solve the problem. From the research was known that the Indonesian's road transportation context helps student to understand basic concept of addition and subtraction. The suggestion to further research this context can be used in design research of multiplication.